Effect of Sellers’ Ethical Behavior in Traditional Markets on Tourists’ Souvenir Purchase Intention. Does Ethnocentrism Matter? - Ayad, Tamer Hamdy; Khalil, Rasha Ahmed; Dwedar, Miral Ahmed (Journal of Ecohumanism, 2024)
This study investigates the direct impact of sellers’ ethical behavior "SEB" in traditional markets on tourists’ souvenir purchase intention "TPI", as well as the indirect role of ethnocentrism "ETHNO" on the relationship between the other two variables. Self-administered surveys were provided to a randomly selected sample of tourists as part of the research, which used a quantitative technique. Structural equation modeling (SEM) analysis of 474 valid responses showed substantial positive correlations between "SEB" and "TPI", with "ETHNO" also having a positive effect on "TPI". The study also proved that "ETHNO" moderates the relation between "SEB" and "TPI". These insights offer souvenirs’ sellers and policy-makers insightful advice on how to adapt their behaviors and marketing strategies to enhance the overall shopping experience and cater to the diverse cultural preferences of tourists.